Disability, Policy and Professional Practice. - Harris, Jennifer (SAGE Publications, 2010)
This is the first book on working with disabled people to take an aspirational, outcomes-focused approach to professional practice. It forms the first attempt to grapple with the massive legislative and policy shifts in the Disability field in the last 15 years and provides an up-to-date, positive approach to professional practice, based on the social model of disability. Importantly, the book translates both adult and children's' disability legislation and policy guidance into positive, creative, enabling practice methods for professionals in social care, health, employment and independent li.